An annotated checklist of the Syrphidae (Diptera) of Algeria - Djellab, Siheme; Mebarkia, Nadjoua; Mehalaine, Khadidja; Ricarte, Antonio; Samraoui, Boudjema (Zootaxa, 2026)
Algeria, situated in the southern Mediterranean Basin, is the largest country in Africa and spans a wide gradient of climates and habitats, ranging from Mediterranean coastal plains and mountain ranges to high steppe plateaux, sandy formations, and Saharan plateaux. This marked environmental heterogeneity provides suitable conditions for hoverflies (Diptera: Syrphidae) across a wide spectrum of terrestrial and aquatic habitats. Despite this diversity, the hoverfly fauna of Algeria remains poorly known. Here, we update the current knowledge of Algerian Syrphidae by compiling all published records and adding new data obtained from recent fieldwork in northeastern Algeria. A preliminary checklist of 128 species in 43 genera is presented. Among these, Mesembrius peregrinus (Loew) is recorded for the first time from Algeria. The updated checklist includes taxa with diverse larval ecologies, including saproxylic species associated with forested habitats such as Brachypalpus valgus (Panzer) and Spilomyia maroccana Kuznetzov, phytophagous species such as Merodon calcaratus (Fabricius) and Eumerus etnensis van der Goot, predatory species such as Eupeodes nuba (Wiedemann) and Paragus vandergooti Marcos García, and saprophagous aquatic species such as Eristalinus taeniops (Wiedemann) and Eristalis arbustorum (Linnaeus). Given the size of Algeria and the breadth of habitats available to Syrphidae, the number of recorded species is expected to increase with further targeted surveys, particularly in poorly explored regions of the country.